2021
DOI: 10.7150/ijbs.59891
|View full text |Cite
|
Sign up to set email alerts
|

Roquin2 suppresses breast cancer progression by inhibiting tumor angiogenesis via selectively destabilizing proangiogenic factors mRNA

Abstract: Tumor angiogenesis is an essential step in tumor growth and metastasis. The initiation of tumor angiogenesis is dictated by a shift in the balance between proangiogenic and antiangiogenic gene expression programs. Roquin2 is a zinc-finger RNA-binding protein with important roles in mediating the expression of inflammatory genes, such as TNF , IL6 and PTGS2 , which are also important angiogenic factors. In this study, we demonstrate that Roqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Interestingly, when subdividing the control group into subgroups according to the origin of the renal biopsies, our IHC results showed a high expression of Regnase-1 and Roquins especially in non-malignant regions of the biopsies taken from nephrectomy specimens, unlike autopsy biopsies. This observation suggests the involvement of these RBPs in renal cancer pathology as supported by other studies, which revealed an important role of Regnase-1 in the regulation of angiogenesis and metastasis of renal cell carcinomas [ 30 ], and have involved the Roquins role in tumor suppression [ 31 , 32 ]. On the other hand, Pospiech et al hypothesized that variation in ZC3H12A may be associated with the risk of clear cell renal cell carcinoma development [ 30 ].…”
Section: Discussionsupporting
confidence: 71%
“…Interestingly, when subdividing the control group into subgroups according to the origin of the renal biopsies, our IHC results showed a high expression of Regnase-1 and Roquins especially in non-malignant regions of the biopsies taken from nephrectomy specimens, unlike autopsy biopsies. This observation suggests the involvement of these RBPs in renal cancer pathology as supported by other studies, which revealed an important role of Regnase-1 in the regulation of angiogenesis and metastasis of renal cell carcinomas [ 30 ], and have involved the Roquins role in tumor suppression [ 31 , 32 ]. On the other hand, Pospiech et al hypothesized that variation in ZC3H12A may be associated with the risk of clear cell renal cell carcinoma development [ 30 ].…”
Section: Discussionsupporting
confidence: 71%
“…EDN1 has been shown to be overexpressed in a variety of solid tumors [ 30 – 33 ]. Endothelins (EDNS) had three subtypes: EDN1, EDN2, and EDN3.…”
Section: Discussionmentioning
confidence: 99%
“…PDGF promotes angiogenesis by enhancing VEGF and PDGF signaling and VEGF gene expression and activating PDGF receptors (PDGFRs), or by upregulating stromal VEGF [ 12 ]. In particular, PDGF-C is a potent mediator of cell migration, growth, survival, transformation, apoptosis, tissue development, and wound healing; stimulates Ewing’s sarcoma proliferation; and induces paracrine signaling events in whole tumor lysates [ 13 , 14 ]. Moreover, a significant positive correlation exists between PDGFR-α and chondrosarcoma tumor aggressiveness [ 15 ].…”
Section: Introductionmentioning
confidence: 99%